Emotional Design of Interior Spaces: Exploring Challenges and Opportunities - Liang Rui; Muhammad Firzan (Buildings)
At present, the integration of cultural and emotional aspects in interior designs is considered to be crucial. The combined emotional and new Chinese decorative style effects of interior spaces have not been examined adequately in previous studies. Thus, this study focuses on the role of new Chinese decorative elements in influencing emotional aspects within the context of interior design in China. To fulfil this aim, a qualitative approach was utilized. For this purpose, the data is gathered in two phases. In phase I, semi-structured interviews were utilized to collect data from 5 interior designers. In phase II, data was collected from a focus group discussion with 6 experts. Nvivo 12 software was used for conducting a thematic analysis of the collected transcripts within the context of interview strategy. However, for focus group discussion, content analysis was conducted. The findings from five interior designers showed that emotional aspects in interior designs are impacted by cultural elements. Moreover, numerous challenges in interior design can be overcome by the integration of emotional strategies. The results have shown that the emotional and cultural aspects are crucial for the development of creative interior spaces. Three levels of emotional design have been identified from focus group discussion. Visual aesthetic level comprises of novelty, color conformity, order and sequence, and richness of design. Three main functional levels are usability, comfort, and privacy. Individual level consists of culture, personalization, and fashion elements. Therefore, this study can be effective in promoting the development of creative interior spaces with a comprehensive focus on the levels of emotional design in the context of the new Chinese decorative style.